Addiction Recovery Among Opioid-Dependent Patients Treated With Injectable Subcutaneous Depot Buprenorphine: Study Protocol of a Non-randomized Prospective Observational Study (ARIDE) - Schulte, Bernd; Lehmann, Kirsten; Schmidt, Christiane Sybille; Rühling, Elke; Weber, Bernd; Schäfer, Ingo; Reimer, Jens; Verthein, Uwe (Frontiers in Psychiatry, 2020)
Introduction Once-weekly or once-monthly injectable depot buprenorphine is a new opioid substitution treatment (OST) medication that provides clinically relevant plasma concentrations without daily peaks. Together with a high tolerability and acceptance reported by patients, the prolonged release of injectable depot buprenorphine might have beneficial implications on the patients’ quality of life and social participation. The primary objective of this prospective non-interventional observational study is to evaluate the effects of subcutaneous injectable depot buprenorphine on the quality of life of patients in routine OST care in Germany. Secondary outcomes like illicit substance use, psychological distress, social participation and activity are assessed to provide an overall evaluation towards addiction recovery. Methods and analysis The present study is a non-randomized prospective observational study with a control group (treatment-as-usual). To ensure comparability between both patient groups, suitable control patients (n = 213) from the same OST unit will be matched pairwise to each patient treated with injectable depot buprenorphine (n = 213). Matching variables are gender, duration of OST, take-home prescription and psychosocial functioning (according to the Global Assessment of Functioning scale). Primary study endpoint is the difference of change in quality of life, assessed with the recently developed Opioid Substitution Treatment Quality of Life scale (OSTQOL), within the depot buprenorphine group between baseline and month 12. The primary analysis will be carried out according to the intention-to-treat principle (ITT) by comparing OSTQOL mean scores using dependent t-tests. For secondary analyses, group comparisons will be done by mixed model approaches with baseline OSTQOL score and the (pairwise) cluster term as covariates. Discussion The study combines clinical, routine OST care data with relevant patient reported outcome data. The pairwise matching allows conclusions on effects of different OST medications. The study findings will provide new insights in the addiction recovery processes of OST patients treated with depot buprenorphine. Ethics and dissemination The study protocol has been approved by the Ethics Committee of the Hamburg Chamber of Physicians (Ärztekammer Hamburg) (reference number: PV7078). The study results will be disseminated through peer-reviewed publications and presentations on scientific conferences.